Does information opacity suppress qualified foreign institutional investor (QFII) investment? Evidence from QFII decisions in the a-share market - Yaojing, Yang; Abdul Aziz, Nor Farradila (Universiti Teknologi MARA Selangor, 2026)
Since the removal of Qualified Foreign Institutional Investor (QFFI) quotas in 2019, foreign capital has become a pivotal long-term investor in China’s A-share market; yet systematic evidence on whether these institutions screen firms for information transparency at the micro level remains scarce. Examining 15,216 firm-year observations from 2019 to 2023, we proxy information opacity by the sum of absolute discretionary accruals over the preceding three years and estimate a Logit model of annual QFII holding decisions. A two-sample t-test shows that firms held by QFIIs exhibit significantly lower opacity than those not held, while the Logit results indicate that a one-unit increase in opacity reduces the probability of QFII ownership by 1.102 percentage points. These findings demonstrate that transparency serves as a primary threshold for foreign entry. Accordingly, regulators should therefore strengthen disclosure requirements, while firms should curtail earnings management, to enhance A-share attractiveness to long-horizon foreign capital and bolster China’s global market competitiveness.